Introduction of verticulture technique for utilization of spring land in Madrasah Tsanawiyah (MTS) ibnu sina City of Pematangsiantar - Sihombing, Yuan Alfinsyah; Susilawati; Sinaga, Muhammad Zulham Efendi (Talenta Publisher, 2019)
The area of agricultural land tends to decrease each year due to land conversion. In 2009 the area of land was reduced by 97 hectares. This is because the land is allocated to non-agricultural land. In urban areas, with all the busyness faced by people in urban areas they do not have time to farm. Moreover, not enough land is available or has no room to come into contact with agricultural cultivation. Not to mention that we often see dwellings that are quite dense and save land, how to foster hobbies and agricultural businesses, especially for housewives, teenagers or retirees? Currently various methods are carried out in line with technological developments. Verticulture is a technique of farming in a room / narrow land by utilizing a vertical plane as a place for farming which is carried out in stages. The purpose of verticulture is to make optimal use of narrow land. The stages of this implementation are the Socialization of Verticulture Cultivation Techniques at Ibnu Sina MTs, Assistance and the process of planting verticultural cultivation techniques, Evaluation and gift giving as awards to students and schools. The results achieved in this community service are products or goods produced in the form of verticulture, this socialization service is carried out in practice so that participants, students and teachers, can understand the techniques of plant cultivation with verticultural techniques as well as good planting and maintenance methods, Plant cultivation techniques with vertikultus techniques and ways of planting and good care have been understood by students in Madrasah Tsanawiyah (MTs) Ibnu Sina, Pematangsiantar City and have been well implemented.